Respuestas

2012-03-05T16:32:18+01:00

2(2x+10)=10 ---> 4x+20=10 --->4x+10=0 ---> x=-10/4 ---> x= -5/2

 

---------------------------------------------------------------------------------

 

(4x-5)/4+2=2 ---> (4x-4)/4=0 ---> 4x-4=0 ---> x=4/4 ---> x=1

 

---------------------------------------------------------------------------------

 

(x-3)^2+5=1 ---> x^2 -6x+9 +4=0 --->x^2-6x+13=0

 

Aplicamos la fórmula de ecuaciones de segundo grado y queda:

X1= no existe porque no hay cuadrado que de negativo

X2= "       "       "         "     "       "          "     "       "